2021
DOI: 10.7759/cureus.20698
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome Among Female Adolescents With Congenital Adrenal Hyperplasia

Abstract: Objectives: Polycystic ovary syndrome is a common endocrine disease in adolescent females that is usually diagnosed based on clinical and hormonal abnormalities. Female adolescents with poorly controlled congenital adrenal hyperplasia are at increased risk of developing polycystic ovary syndrome. This study aimed to determine the prevalence of polycystic ovary syndrome and assess its relationship with hormonal control among adolescents with congenital adrenal hyperplasia. Methods: This retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Early onset adiposity has been implicated in the pathogenesis of PCOS and can be predictive of a more severe phenotype. It is also linked to the development of low-grade inflammation, greater cardiometabolic dysfunction and future risk of atherosclerosis [ 12 - 15 ]. Our data shows that as an indicator of visceral fat function, VAI correlates well with severity of menstrual dysfunction and ovarian dysmorphology, and seems to be predictive of impaired glucose tolerance, thus indicating propensity for development of diabetes in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early onset adiposity has been implicated in the pathogenesis of PCOS and can be predictive of a more severe phenotype. It is also linked to the development of low-grade inflammation, greater cardiometabolic dysfunction and future risk of atherosclerosis [ 12 - 15 ]. Our data shows that as an indicator of visceral fat function, VAI correlates well with severity of menstrual dysfunction and ovarian dysmorphology, and seems to be predictive of impaired glucose tolerance, thus indicating propensity for development of diabetes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that visceral adiposity is linked to the severity of anovulation, insulin resistance and cardiometabolic risk in women with PCOS [ 12 , 16 , 17 ]. We noted that increasing VAI was associated with longer menstrual cycles.…”
Section: Discussionmentioning
confidence: 99%